Efektifitas Media Puzzle Siput Dalam Pengembangan Pembelajaran Matematika Pada AUD - Siti Fitroh; Siti Mardiyah (PG-PAUD Trunojoyo, 2015)
The Effectiveness of Media Puzzle Snails in Developing The Learning of Mathematics in Early Childhood. Early childhood aged 3-6 years is the period a child who will receive all the stimuli given to him without any hindrance. At that age the child will develop in accordance with what they get. If the child gets positive stimulus child will develop in a positive direction, and vice versa. Early childhood learning with the real thing, the child will be more likely to do than just listen to the words of others. Media snail puzzle is very help children to learn simple math. Through this medium children learn by playing and participating in the game. Children assigned to pair the puzzle pieces in accordance with the sequence of numbers (1-20). The instrument used is by using observation, data collection in the form of descriptive. This observation sheet contains records that describe the learning activities in the classroom. observation sheet format used is the systematic observation sheet-shaped fields to determine the action during the learning process. Results of studies suggest that media puzzle as being effective in the learning of mathematics in early childhood.